ANALISIS PERSEPSI DAN TINGKAT KEPUASAN KONSUMEN TERHADAP PEMBELIAN AYAM BROILER ORGANIK DI KOTA PEKANBARU (Fakultas Pertanian, Universitas Riau, 2023)
The livestock sub-sector is an integral part of the broad development of the agricultural sector as a source of animal protein that has the potential to be developed is broilers. Given the trend of healthy living among the community by consuming organic food such as organic broiler chicken. This study aims to: 1. determine the characteristics of consumers who buy organic broiler chicken in the city of Pekanbaru 2. analyze consumer perceptions in purchasing organic broiler chicken in the city of Pekanbaru. 3. Analyze the level of consumer satisfaction in purchasing organic broiler chickens in Pekanbaru City. This study uses a survey method through questionnaires with sampling using the proportional random sampling. The results of the research on the characteristics of consumers of organic chicken meat, namely female sex as many as 69 people (86.25%) with ages 30-49 years as many as 57 people (71.25%) with a bachelor's degree (S1) education as many as 52 people (65%), income > 5,000. 000,- as many as 33 people (51.25%), the type of work of housewives as many as 41 people (51.25%), the frequency of purchasing 2-3 times a month as many as 38 people (47.5%) with the weight of meat in each purchase of 1-1.5 kg as much as 66 people (82.5%), with an expenditure of IDR 200,000 - < IDR 300,000, - for each purchase of 43 people (53.75%), the nutritional content of organic chicken meat is the reason for purchasing 38 people (47.5%) with consideration of the place purchase due to the quality of the product at that place as many as 33 people (41.25%). The consumer's perception with the highest score on the variable benefits of meat is 4.68. The CSI value is 84.44% with the purchase category being very satisfied, while the IPA analysis obtained is the intended location and stock of chicken meat.